Islam: Dialogue, Devotion, and Development (American Journal of Islam and Society, 2004)
ISNA’s Forty-first Annual Convention, held in Chicago (September 4-6,2004), offered about 100 sessions and was cohosted by the Council ofIslamic Organizations of Greater Chicago (CIOGC). Over 400 ChicagoMuslim volunteer organizations offered their support, resources, and talentsunder CIOGC’s leadership. The Friday night Interfaith Unity Banquetwas dedicated to interfaith dialogue. The invitation-only event seeks toenergize attendees, including politicians running for office in the Chicagoarea, to continue their efforts and to recognize those who are trying to buildbridges between different faith communities. The Rev. Stanley L. Davis, Jr.,was given a plaque for his continuing work in interfaith relations plus hisdedication to peace and justice.The Fifth Annual Community Service Recognition Luncheon, hosted bythe ISNA Development Foundation, was addressed by Cherif Bassiouni, arespected attorney and professor at DePaul University, who is also presidentof the International Human Rights Law Institute. He declared: “It makes meangry when Muslims apologize for Islam. I am proud to be a Muslim.”For the first time, a female Muslim activist, Sharifa Alkhateeb, receivedthe Mahboob Khan Community Service Award, which recognizes outstandingservice to the Muslim community in North America. Alkhateeb, recognizedfor her work in various causes, especially those concerning women,could not attend. Her husband Mejdi accepted the award on her behalf, whileher sister read her acceptance speech. Former ISNA president MuzammilSiddiqui also received the award ...